2014
DOI: 10.1021/ac501470p
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar Detection Limits of Cd2+, Ag+, and K+ Using Paper-Strip Ion-Selective Electrodes

Abstract: Paper-based ion-selective electrodes (ISEs) are simple, flexible, and cost-efficient in comparison to conventional solid-contact ISEs. Yet, paper-based ISEs have poor limits of detection (in the micromolar range) relative to conventional solid-contact ISEs. Here we describe the construction and optimization of ISEs based on commercially available filter paper modified with single-walled carbon nanotubes (SWCNTs), sputtered gold, and conductive polymer poly(3-octylthiophene) to support an ion-selective membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 43 publications
6
70
1
1
Order By: Relevance
“…7,16 Interestingly, other reports indicate that presence of sputtered gold and conductive polymer such as poly(3-octylthiophene) is necessary to produce stable paper based ISEs. 5 This discrepancy between reported data could perhaps arise from differences in the thickness of CNTs layer deposited onto the paper surface, the concentration of surfactant (unwashed surfactant may reduce contact angle between water droplet and the substrate, thus increasing surface wetting) 17 and purity of used materials. However, to produce functional sensing devices, CNTs have to be typically dispersed in a liquid [18][19][20] (often water and surfactant solution) via ultrasonication and are later deposited onto the paper/electrode by drop-casting, 21,22 ink-jet printing, [23][24][25] dip-coating [26][27][28] or spin coating.…”
Section: -15mentioning
confidence: 93%
See 1 more Smart Citation
“…7,16 Interestingly, other reports indicate that presence of sputtered gold and conductive polymer such as poly(3-octylthiophene) is necessary to produce stable paper based ISEs. 5 This discrepancy between reported data could perhaps arise from differences in the thickness of CNTs layer deposited onto the paper surface, the concentration of surfactant (unwashed surfactant may reduce contact angle between water droplet and the substrate, thus increasing surface wetting) 17 and purity of used materials. However, to produce functional sensing devices, CNTs have to be typically dispersed in a liquid [18][19][20] (often water and surfactant solution) via ultrasonication and are later deposited onto the paper/electrode by drop-casting, 21,22 ink-jet printing, [23][24][25] dip-coating [26][27][28] or spin coating.…”
Section: -15mentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10] This versatile character can be attributed to their excellent electrical conductivity, high tensile strength and ability to function simultaneously as recognition element and transducer (transduction via the formation of electrical double layer).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Mensah et al further reported nanomolar detection limits of another type of paper-strip ISE constructed from carbon-nanotube-modified filter paper, sputtered gold, conductive polymer, and an ISM. 13 In another report, Bobacka and co-workers performed potentiometric measurements by pressing solid-contact electrodes against sample-impregnated filter paper. 14 Neither of these approaches used wax-imprinted paper to define a more fully integrated paper-based potentiometric cell.…”
Section: T He Selective Quantitation Of Electrolyte Ions In Solution Ismentioning
confidence: 99%
“…[1][2][3][4][5] With a view to miniaturization, mass fabrication and measurements in small volumes, solid-contact ion-selective electrodes (SC-ISEs) with a solid inner contact as the ion-to-electron transducer, have been receiving much attention.…”
mentioning
confidence: 99%